Knowledge of child sexual abuse and attitudes towards reporting it among teachers and parents of children studying in selected primary schools of Udupi Taluk, India - Shwetha Prabhu; Savitha Prabhu; Flavia Noronha (Egyptian Journal of Forensic Sciences, 2023)
Abstract Background Child sexual abuse is one of the major issues of concern globally. Teachers and parents being the child’s primary caregivers should be knowledgeable regarding child sexual abuse. Aim of the study This study aimed to assess knowledge about child sexual abuse, determine attitudes toward reporting child sexual abuse, and find the relationship between knowledge and the attitude among the teachers and parents of the children studying in selected primary schools of Udupi taluk. Methods A descriptive survey design was adopted; the study participants were 90 teachers and 50 parents of the children studying in selected primary schools of Udupi Taluk. The instruments used were demographic proforma, a structured knowledge questionnaire about child sexual abuse, and an attitude scale toward reporting it. Results Results depicted that 50% of the teachers had average knowledge and 50% had good knowledge about child sexual abuse. All the teachers reported a favorable attitude towards reporting child sexual abuse. Similarly, 80% of the parents had average knowledge about child sexual abuse, and a majority of 76% had a favorable attitude towards reporting child sexual abuse. Unfavorable attitude towards reporting child sexual abuse was reported by 24% of the parents. No statistically significant correlation was found between knowledge and attitude toward reporting child sexual abuse among parents ((χ 2 = 1.891, p = 0.388). A significant association was found between teachers’ knowledge scores, their previous knowledge about child sexual abuse (χ 2 = 7.56, p = 0.006), and the existence of a school counselor (χ 2 = 5.40, p = 0.020). Likewise, the association was found between parents’ knowledge score, educational level of parents (χ 2 = 18.3, p = 0.019), and marital status (χ 2 = 18.5, p = 0.005). Conclusion Child sexual abuse is one of the major issues of concern globally. Teachers and parents being the child’s primary caregivers should be knowledgeable regarding child sexual abuse. As parents are not exposed to any training regarding identifying and reporting child sexual abuse, they may have unfavorable attitudes toward reporting it.